Amiga the computer that wouldn't die. - Wallich, P.
In this paper, the author describes how, having outlived a number of its corporate owners, and spurred on by its passionate users, the Amiga computer is going back to market again-but this time, in very different forms
Keywords: Amiga computer; Market; Product developments